Energy as the cornerstone of environmentally driven sex allocation. (October 2022) - Geffroy, Benjamin
Abstract : In recent years, observations of distinct organisms have linked the quality of the environment experienced by a given individual and the sex it will develop. In most described cases, facing relatively harsh conditions resulted in masculinization, while thriving in favorable conditions promoted the development of an ovary. This was shown indistinctively in some species presenting a genetic sex determination (GSD), which were able to sex-reverse, and in species with an environmental sex determination (ESD) system. However, this pattern strongly depends on evolutionary constrains and is detected only when females need more energy for reproduction. Here, I describe the mechanisms involved in this environmentally driven sex allocation (EDSA), which involves two main energy pathways, lipid and carbohydrate metabolism. These pathways act through various enzymes and are not necessarily independent of the previously known transducers of environmental signals in species with ESD: calcium–redox, epigenetic, and stress regulation pathways. Overall, there is evidence of a link between energy level and the sexual fate of individuals of various species, including reptiles, fish, amphibians, insects, and nematodes. As energy pathways are evolutionarily conserved, this knowledge opens new avenues to advance our understanding of the mechanisms that allow animals to adapt their sex according to the local environment. Highlights: The quality of the environment directly or indirectly influences the sex of a variety of species. The phenotypic sex of some animals is linked to energy level at a given, key moment. Regulation of lipid and carbohydrate metabolism is involved in the process. This change in metabolism is accompanied by changes in stress hormone levels and epigenetic modifications. Findings in invertebrates, fish, amphibians, and reptiles open new avenues in our understanding of sex allocation in mammals.